Analysis of Brand Preference of Soft drinks in the Global Environment - Kaushik, Rajiv (Indian Journal of Marketing, 2006)
The PVC industry, which made a modest beginning during 70’s had really taken off during the post liberazation era. The current business environment and abundant domestic availability of PVC raw materials have resulted in double digit growth rate during the recent years. In 2000-2001, the growth in PVC consumption was about 12%. More over it is estimated that about Rs. 20000 crores has been invested during 1997-2000 in this industry, leading to doubling of capacity. Continued growth in consumption at this rate would make India 3rd largest PVC consumer in world by 2010. At present per capita consumption of PVC in India is just 3.5 kg as compared to the global average of 19 kg. Hence there is great scope for this industry in India.